ESP Need Analysis of Computer and Network Engineering in Vocational High School - Tri Nurhasanah; Eri Kurniawan (J-SHMIC : Journal of English for Academic, 2023)
A vocational school is an educational institution that focuses on providing students with practical skills and training for specific careers or professions. Unfortunately, the English lessons given to vocational schools still follow the same English as English in general high school which does not support their needs in their specific major resulted in gaps in English skill for vocational students. The gaps between secondary schools teaching English and vocational schools in terms of resources, curriculum, and even infrastructure. Examining the ESP of computer and network engineering in vocational high school was the aim of this study. As research tools for this study, a questionnaire about needs analysis, analysis of textbooks, and analysis of interviews were used. The findings indicated that in vocational schools, ESP teaching and learning based on the school program is needed by both students and teachers. The poor value of English language proficiency, particularly ESP in vocational schools, is due to a number of factors, including a lack of ESP for computer and network engineering starting from the content, such as textbooks, suitable school facilities, and even the competence of teachers to teach ESP.